Non-invasive Prenatal Diagnosis of Single Gene Disorders by Paternal Mutation Exclusion: 3 Years of Clinical Experience. Issue 4 (April 2023) - Pacault, Mathilde; Verebi, Camille; Lopez, Maureen; Vaucouleur, Nicolas; Orhant, Lucie; Deburgrave, Nathalie; Leturcq, France; Vidaud, Dominique; Girodon, Emmanuelle; Bienvenu, Thierry; Nectoux, Juliette
ABSTRACT: Until recently, fetal genetic testing was possible only via invasive sampling (amniocentesis or chorionic villus sampling). Although such testing allows for prenatal diagnosis (PND) of inherited monogenetic disorders, it is also associated with a risk of miscarriage. Identification of cell-free fetal DNA (cfDNA) from maternal circulation allows for noninvasive fetal sex determination and detection of the common aneuploidies. In fact, the entire fetal genome is represented within the circulating cell-free DNA. Clinical services are now available that provide noninvasive PND for monogenetic disorders, although these remain sparse, and most tests of this nature focus on paternally inherited disorders, given that the fetal DNA is diluted by maternal haploidentical sequences. This study reports on an experimental protocol for droplet digital polymerase chain reaction for paternal pathogenic or de novo variants. Since then, this noninvasive PND service has been offered to couples at risk of monogenic disorders in the fetus who have requested PND as a part of standard care. This report summarizes 3 years of clinical experience. Referral indications included the following: those with 50% risk of transmission of an autosomal dominant disorder from the father, those at 25% risk of autosomal recessive disorders and with different parental pathogenic variants such that they could assess for inheritance of the paternal variant, and those at risk for single-gene disorders due to de novo variants based on evident skeletal dysplasia by ultrasound or possible parental germinal mosaicism in a previously affected child. As a matter of practicality and organization, only ongoing pregnancies had new assays designed and ordered. Local French law regarding prenatal genetic testing requires written consent from both parents. Blood from each pregnant woman and blood samples from both parents for extraction of conventional genomic DNA were also collected. Each new variant required creation of a new assay, whose performance was evaluated. All results were reported with summarized interpretations to the clinicians, and invasive diagnostic testing was recommended in cases of autosomal recessive variant identification where inheritance of the paternal variant was detected to identify maternal inheritance. Sampling errors and identity swaps were ruled out by taking a second sample for every negative result. Development of new assays took 7 to 43 days, and overall, these assays were designed to detect 57 individual variants in 16 genes. A result was obtained for all but 2 cases; these were unsuccessful because of a low proportion of fetal DNA. In the autosomal dominant cases, 27% found fetal inheritance of the paternal variant, whereas 73% ruled out such inheritance. In the autosomal recessive cases, the paternal variant was detected in 56% and not detected in the remainder. In cases in which the paternal variant was detected, invasive diagnostic testing was recommended to determine maternal inheritance and whether the fetus was affected. The single inconclusive result was from a pregnancy obtained after egg donation in which ultimately the egg donor and the father both had the same gene variant, making accurate assessment not possible. There were 198 referrals overall, including 22 referrals due to concern for autosomal dominant disorders, 69 due to risk for an autosomal recessive disorder, and 107 due to concern for a de novo variant either because of ultrasound findings or a family history. There were 202 tests performed for 175 different families. All results reported were considered valid, and there were no false-positive results following invasive sampling for maternal inheritance, and no false-negative results reported following delivery. A limitation of this technique is that it addresses only the paternal variant's fetal status. This approach does not allow testing for all types of disease-causing variations such as repetitive elements, copy number variations, or structural variants. Also, maternally transmitted diseases or recessive conditions with both parents as carriers are also not detectable through this method. In the case of multiple pregnancies, there is no method for determining which twin (or whether both twins) will carry the variant. This test allows couples to avoid the risk of miscarriage while being able to make informed decisions about the pregnancy management. In addition, as new treatments are developed for common disorders (CFTR modulators, gene-replacement therapies, uterine genic therapies, and splicing-modifying therapies), the prenatal testing landscape can be expected to drastically evolve to favor a noninvasive approach.